Flexible Electrochemical Biochip Array of Patterned Gold on Silver Inkjet Printed Polyimide. (7th July 2017) - Beggiato, Matteo; Pandey, Richa; Sverdlov, Yelena; Inberg, Alexandra; Demarchi, Danilo; Shacham-Diamand, Yosi
Abstract : Flexible electrodes for bio-electrochemical sensing were fabricated using state-of-the-art inkjet printing followed by two consecutive gold plating steps. Silver nanoparticle printed thin film (1.5μm thick) was sintered at 300°C for 30 minutes and used as seed for the electroless plating of gold (2μm). A further gold electroplating layer was then applied allowing good electrode properties overcoming the printed film roughness and porous morphology which the electroless plating step could not fully cover. The various layers as well as their composite were investigated using electrical, electrochemical and analytical techniques. Eventually, the final electrode was tested with a 3-electrodes setup in a chronoamperometric experiment to detect the Alkaline Phosphatase enzyme in presence of its substrate, ρ -Aminophenyl Phosphate. The electrodes demonstrated a sensitivity of 11.8μA/mM and a limit of detection of 0.9mM.